Korespondencja (1951)
Listy od następujących, Sko.-Sku.: Skorecka, Klotylda 28.02-25.10.1965 (2) k. 1-2. - Skorupczyna, Stanisława 04.02.1973 (1) k. 3. - Skowroński, Zdzisław 27.11.1951-15.03.1961 (16) k. 4-19. - Skrzyp, Adam 09.10.1970 (1) k. 20. - Skufiewski, Stefan 03.11.1958 (1) k. 21. - Skuszanka, Krystyna 30.04-25.09.1965 (4) k. 22-26. - Sławiński, Jan k.
a 1978 601
Keywords: Wrocław (woj. dolnośląskie); Państwowe Teatry Dramatyczne